Lhermitte Duclos disease: a rare cerebellar lesion with characteristic neuroimaging features - Gupta, Pankaj Kant; Garg, Sunil; Thanvi, Sharad (International Journal of Research in Medical Sciences, 2017)
Lhermitte-Duclos disease (dysplastic cerebellar gangliocytoma) is a rare disorder of uncertain pathogenesis characterized by disarrangement of the normal cerebellar laminar cytoarchitecture. A case of histopathologically confirmed Lhermitte-Duclos disease with characteristic imaging findings and successful surgical management is reported and our findings are discussed.